Effect of Fresh Orange Juice Intake on Physiological Characteristics in Healthy Volunteers - Asgary, Sedigheh (Hindawi Publishing Corporation, 2014)
Background. Impaired endothelial function is a predictor of cardiovascular events. Orange juice (OJ) is rich in dietary flavonoids and could inhibit oxidative stress and inflammatory responses. We examined the effects of commercial (COJ) and fresh orange juice (FOJ) on endothelial function and physiological characteristics in healthy humans. Materials and Methods. Twenty-two healthy volunteers years were enrolled in a single blind randomized crossover controlled trial. The two groups consumed either COJ for the first 4 weeks and then FOJ (CFOJ, 4 weeks), or FOJ for the first 4 weeks and then COJ (FCOJ, 4 weeks). We assessed endothelial function by measuring flow-mediated dilation, serum concentrations of lipids, apolipoproteins A and B (apo A-1 and apo B), and inflammatory markers such as vascular endothelial adhesion molecule 1 (VCAM-1), E-selectin, high-sensitivity C-reactive protein (hs-CRP), and interleukin-6. Results. Consumption of both juices decreased VCAM, hs-CRP, and E-selectin but increased apo A-1. A decline in LDL occurred in the FOJ group. There were no differences between the characteristics of two groups, with the exception of apo A-1 levels that were increased with both forms of OJ. The largest variations occurred with hs-CRP, VCAM in both groups. Conclusion. Consumption of COJ and FOJ produced beneficial effects on the physiological characteristics of healthy volunteers. Although these results could encourage the consumption of OJ, intervention studies are needed to determine the long-term effects of these types of OJ on metabolic and cardiovascular endpoints.